Therapeutic Justice Crime, Treatment Courts and Mental Illness - Snedker, Karen A. (Springer International Publishing, 2018)
This book examines Mental Health Courts (MHC) within a socio-legal framework. Placing these courts within broader trends in criminal justice, especially problem-solving courts, the author draws from two case studies with a mixed-methods design. While court observational and interview data highlight the role of rituals and procedural justice in the practices of the court, quantitative data demonstrates the impact of incentives, mental health treatment compliance and graduating patterns from MHC in altering patterns of criminal recidivism. In utilising these methods, this book provides a new understanding of the social processes by which MHCs operate, while narrative stories from MHC participants illustrate both the potential and limitations of these courts. Concluding by charting potential improvements for the functioning and effectiveness of MHCs, the author suggests potential reforms and 'best practices' for the future in tandem with rigorous analysis. This book will be of value and interest to students and scholars of criminology, law, and social work, as well as practitioners.